THE CO2-H2O SYSTEM. I. EXPERIMENTAL DETERMINATION OF VOLUMETRIC PROPERTIES AT 400°C, 10-100 MPA - A REVIEW OF P-V-T-X DATA AND AN ASSESSMENT FROM A PHASE-EQUILIBRIUM POINT OF VIEW - Seitz J.C.; Blencoe J.G. (My University, 1999)
Densities of pure CO2 and CO2-H2O mixtures were experimentally determined at 400°C, 10-100 MPa. The data were obtained with a custom-designed high-pressure, high-temperature vibrating-tube densimeter. Conservative estimates of accuracy are P, +/- 0.02 MPa, T, +/- 0.05°C, and ρ +/- 0.0005 to 0.0010 g . cm-3 for low- and high-density mixtures, respectively. Excess molar volumes (Vex) for mixtures are continuously positive, increasing sharply from 0 MPa to maximum values near 30 MPa. Above 30 MPa, Vex decreases rapidly with increasing pressure. Peak values for Vex are large, representing up to 37% of total volume. The isobaric data (Vex vs. XCO2) are nearly symmetric at pressures below 10 MPa, but become strongly asymmetric toward H2O with increasing pressure above 10 MPa. The highest degree of asymmetry coincides with P-T conditions at the critical isochore for pure H2O (~29.2 MPa at 400°C). With increasing pressure above 30 MPa, asymmetry of the isobaric data shifts toward CO2. Densities for pure CO2 at 400°C, 10-100 MPa, predicted by published equations of state are in fair to excellent agreement with our experimentally determined densities. Previously published density data for mixtures, and excess molar volumes calculated from equations of state, are generally in poor agreement with our results.